Relationship between salivary fluor concentration and caries index in 12–15 years old children - Vidyana Pratiwi; Dudi Aripin; Ame Suciati Setiawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Dental caries is a bacterial infection leading to dissolution and localized damage of hard tissues. The assessment of caries risk is based on several caries indicators including clinical conditions (DMF-T index), environment (fluor), and general health. Purpose: The objective of this study was to assess the relationship between salivary fluor concentration and caries index in children aging 12–15 years old at SMP Negeri 2 PTPN VIII Pangalengan. Methods: This study is an observational analytical study using crosssectional approach and is conducted in a field trial manner. The study sample consists of 80 students in the age of 12 to 15 years old at SMP Negeri 2 PTPN VIII selected through Probability Sampling manner using simple random sampling method. Results: The result of this study shows a DMF-T index of 4.32 and salivary fluor concentration mean of 0.018. Pearson Product Moment correlation test shows that there is a weak correlation between salivary fluor concentration and DMF-T index. Conclusion: It is concluded that the salivary fluor concentration has an insignificant correlation with the DMF-T index since the fluor concentration in saliva is very low.Latar belakang: Karies gigi adalah penyakit infeksi bakteri yang berakibat pada disolusi dan kerusakan terlokalisasi jaringan keras. Penilaian risiko karies berdasarkan atas beberapa indikator karies yaitu kondisi klinis (indeks DMF-T), lingkungan (fluor), dan kesehatan umum. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan konsentrasi fluor yang terdapat dalam saliva dengan indeks karies pada anak usia 12-15 tahun di SMP Negeri 2 PTPN VIII Pangalengan. Metode: Jenis penelitian ini adalah penelitian analitik observasional dengan pendekatan cross sectional yang dilakukan di lapangan. Sampel penelitian sebanyak 80 orang siswasiswi usia 12–15 tahun di SMP Negeri 2 PTPN VIII Pangalengan yang dipilih secara Probability Sampling dengan metode simple random sampling. Hasil: Hasil penelitian menunjukkan indeks DMF-T 4,32 dan rerata konsentrasi fluor dalam saliva sebesar 0,018. Tes korelasi Pearson Product Moment menunjukkan hubungan yang tidak kuat antara konsentrasi fluor dalam saliva dengan indeks DMF-T. Kesimpulan: Dapat disimpulkan konsentrasi fluor dalam saliva mempunyai hubungan dengan indeks DMF-T tetapi tidak signifikan dikarenakan nilai konsentrasi fluor dalam saliva yang sangat rendah.